Die geologische Entwicklung an der Grenze zwischen West- und Ost-Gondwana im atlantischen Sektor Antarktikas - Bauer, Wilfried (Mainz [u.a.], 2010)
The mountains of Dronning Maud Land (DML) cover the area from 18°W to 28°E parallel to the coastline of Antarctica. The ranges occur either as elongate N-S nunatak chains, divided by minor glaciers, or as steep escarpments separating the polar plateau from the ice-covered coastal plains. DML is one of the key regions for Mesoproterozoic to Cambrian plate movement reconstructions. In modern plate reconstructions of the Paleozoic Gondwana supercontinent the southward continuation of the Pan-African aged Mozambique Belt of E-Africa has to be expected in DML. This mobile belt was formed as a result of continent-continent collision following the closure of the Mozambique Ocean, which led to the final amalgamation of West and East Gondwana. The precise position of the collision suture is still under debate. Recent palaeomagnetic, geochronological and aeromagnetic studies show that DML can be subdivided into three distinct areas with different geological histories: (1) an Archaean craton with an undeformed Proterozoic cover; (2) a Late Mesoproterozoic collision orogen and (3) a Pan-African-aged collision orogen with relics of pre-Pan-African structures and voluminous post-tectonic intrusives. In western Dronning Maud Land rocks of a juvenile Mesoproterozoic island arc which was accreted to the Kapvaal-Grunehgna Craton at ~ 1.1 Ga are well documented. Mesoproterozoic rocks were also detected by zircon SHRIMP dating of gneisses further east in central Dronning Maud Land. Tectonothermal events at the end of the Mesoproterozoic and at Late Neoproterozoic/Cambrian times ("Pan-African") have been proved within the metamorphic belt in central Dronning Maud Land, combined with an amphibolite to granulite facies metamorphism and syntectonic granitoid emplacement. During this orogeny older structures were completely overprinted in a sinistral tranpressive deformation regime, leading to the mainly coast-parallel tectonic structures of the East Antarctic Orogen. Putting Antarctica back in its Gondwana position, the East Antarctic ...